Relationship between Knowledge and Family Support regarding Hypertension with Blood Pressure Control in Elderly - Kusumawardana, Iin; Tamtomo, Didik; -, Sugiarto (Indonesian Journal of Medicine, 2017)
Background: Hypertension is one of the degenerative diseases that have frequently been found among the group of elderly. If hypertension goes uncontrolled, then it might escalate and cause complication. The level of knowledge for both of patients and their families in terms of preventive actions toward hypertension complication is expected to be able to control blood pressure. Among the hypertension patients, the role of family support is very important in order to maintain and to control that the blood pressure will not increase and to return it to the normal state. In relation to this background, the objective in conducting this study was to analyze the relationship between knowledge and family support regarding hypertension with blood pressure control among the elderly with hypertension in the Sangkrah Center of Public Health, City of Surakarta.Subjects and Method: This was an analytic observational study with cross sectional design. This study was conducted in Sangkrah Community Health Center in the City of Surakarta on November 2016. A total sample of 147 elderly were selected for this study by purposive sampling. The dependent variables in this study was blood pressure and was measured by sphygnomanometer. The independent variables were knowledge and family support and were collected by a set of questionnaire. The data analyzed by logistic regression.Results: Family knowledge (OR= 0.38; 95% CI= 0.13 to 1.08; p= 0.070) increased the likelihood of blood pressure control. Elderly who came from family with good knowledge regarding hypertension had 0.4 times better blood pressure control in comparison to those who came from family with poor knowledge regarding hypertension. Family support (OR= 0.43; 95% CI= 0.18 to 1.02; p= 0.046) increased the likelihood of blood pressure control. Elderly with good family support had 0.4 times better blood pressure than those who had poor family support.Conclusion: Family knowledge and family support increase the probability of blood pressure control among elderly with hypertension.Keywords: knowledge, family support, blood pressure control, elderlyCorrespondence:ÃÂ Iin Kusumawardana. Masters Program in Family Medicine, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: iinkusuma90@gmail.comIndonesian Journal of Medicine (2017), 2(1): 1-9https://doi.org/10.26911/theijmed.2017.02.01.01